The Custodians of Holy Book In Nigeria - A.M. Abikan, Musa; Muhammad Kamil, Ahmad (Al-Ḍād Journal, 2020)
The Almighty Allah, indeed, bestowed Nigeria with scholars who studied the glorious Qur’an and its sciences meticulously and excellently trough their personal efforts despite the obstacles put forward by the enemies within and outside the country over many centuries. Part of these efforts is that some of these scholars translated the meanings of the Qur’an into Nigerian languages in order to get the proper meaning of the Qur’an clearly by the citizens while some of them did the Tafsir, so that, every Muslim will understand the Holy book with ease. They also innovated divergent ways in order to interest Muslims to study the book across the globe. This research is hereby carried out to solve problems created by foreign colonists in Nigeria and methods used by scholars of the land to conquer or erase many of those problems/challenges. The method applied for this research are; descriptive and historical approaches while findings reveal that Nigeria scholars specifically concern with the teachings of the Qur’an and its sciences over other subjects and honor both scholars and students with specific nicknames and epithets particularly the memorizers and custodians of the Holy Book either in public schools or private institutions.